NILAI KETAKTERATURAN TOTAL SISI DARI GRAF SIPUT - Novindasari, Shapbian; Slamin, S; Dafik, D (Kadikma, 2015)
Abstract. Let G=(V,E) be a simple graph, a labeling is called an edge irregular total k-labelling of G if for any two different edges e and f of G there is, . The total edge irregularity strength denoted by tes G is the smallest positive integer k for which G has an edge irregular total k-labelling. In this paper, we will determine the total edge irregularity strengths of a Snail graph, the union isomorphic and non-isomorphic union of Snail graph, and shackle graph of Snail graph. We show that , for , , for and , , for where natural numbers, and , for and Key Words: Total edge irregular labeling, Total edge irregularity strength, Snail graph.